An Investigation of Sustainable Power Generation from Oil Palm Biomass: A Case Study in Sarawak - Aghamohammadi, N.; Reginald, S.S.; Shamiri, A.; Zinatizadeh, A.A.; Wong, L.P.; Sulaiman, N.M.N. (MDPI, 2016)
Sarawak is the largest state in Malaysia, with 22% of the nation's oil palm plantation area, making it the second largest contributor to palm biomass production. Despite the enormous amount of palm biomass in the state, the use of biomass as fuel for power generation remains low. This study is designed to investigate the sustainability of power generation from palm biomass specifically in Sarawak by conducting a survey among the palm oil mill developers. To conduct this investigation, several key sustainability factors were identified: the security of the biomass supply, the efficiency of conversion technology, the existing network system, challenges and future prospects for power generation from palm biomass. These factors were assessed through a set of questionnaires. The returned questionnaires were then analysed using statistical tools. The results of this study demonstrate that Sarawak has biomass in abundance, and that it is ready to be exploited for large scale power generation. The key challenge to achieving the renewable energy target is the inadequate grid infrastructure that inhibits palm oil developers from benefiting from the Feed-in-Tariff payment scheme. One way forward, a strategic partnership between government and industrial players, offers a promising outcome, depending on an economic feasibility study. The decentralization of electricity generation to support rural electrification is another feasible alternative for renewable energy development in the state.